POLA PENDIDIKAN KELUARGA HINDU DI KELURAHAN SADING KECAMATAN MENGWI KABUPATEN BADUNG - Kadek Ayu Putri Oktaviani; I Nyoman Sueca; Ni Nyoman Mariani (UHN IGB Sugriwa Denpasar, 2020)
The pattern of education is the form, method or variety in educating, especially education in Hindu families. The provision of education is very important to prevent the occurrence of behavioral deviations that are currently rife in society. Each family certainly applies a different education pattern but aims to develop a good personality in children.The formulation of the problem in this study are 1) What is the Education Pattern for Hindu Families in Sading Village, Mengwi District, Badung Regency?, 2) What are the Obstacles Faced in the Hindu Family Education Pattern in Sading Village, Mengwi District, Badung Regency?, 3) What are the Efforts to Face Obstacles in the Pattern? Hindu Family Education in Sading Village, Mengwi District, Badung Regency? The purposes of this study: 1) Describe the Hindu Family Education Pattern in Sading Village, Mengwi District, Badung Regency, 2) To know the obstacles faced in the Hindu Family Education Pattern in Sading Village, Mengwi District, Badung Regency, 3) To describe the efforts to face obstacles in the Hindu Family Education Pattern in Sading Village, Mengwi District, Badung Regency. The theory used in this research is the theory of behavioristic, phenomenological, and constructivist. The data collection method used is the method of observation, interviews, literature study, and documentation study. The informants in this study were Hindu families in Sading Village. The results obtained are 1) Hindu Family Education Patterns in Sading Village, Mengwi District, Badung Regency, namely religious education patterns, ethical education patterns, satya education patterns, education patterns with exemplary, education patterns with habituation, and education patterns with advice 2) Obstacles that faced in the pattern of Hindu family education in Sading Village, Mengwi District, Badung Regency, consists of internal factors and external factors 3) Efforts to overcome obstacles in the pattern of Hindu family education in Sading Village, Mengwi District, Badung Regency are the Bayuh Oton ceremony, giving attention and affection to the family. children, facilitating children's creativity and limiting the use of technology.